Upaya Meningkatkan Pengurangan Limbah Minyak Goreng Menjadi Produk UMKM Lilin Aromaterapi Sebagai Ide Kreatif Kampung Mojo RW.10 RT.02 Kota Surabaya - Winne Ayunda Gaiska; Muhammad Yasin (Universitas Muhammadiyah Manado, 2024)
Recycling is the processing of waste or remaining waste products into new products that can be used appropriately again with one of the goals being to preserve the environment. This community service is carried out by selecting household waste objects in the form of utilizing cooking oil waste into a useful material that will reduce the negative impact of used cooking waste. The public's lack of understanding and knowledge about how to process these remaining materials, turns used objects into less useful items so that many are thrown away and not used and can also reduce plastic waste. The use of smartphones presents a great opportunity to promote products through social media. In this research, a digital marketing promotion strategy was implemented through social applications. This service activity will discuss one of the business opportunities that can be done on a home scale with opportunities that are quite promising at the moment, namely the use of used cooking oil as raw material for aromatherapy candles. By implementing the right marketing strategy, it can help reach a wider consumer market so that new potential consumers come in who are willing to visit the stand and buy the product. By designing attractive digital promotions, the brand appearance of the product will also be more easily recognized by the public. Strategies that can be carried out by MSMEs Keywords: used cooking oil, SMEs, aromatherapy candles,